Tontura e diabetes mellitus em idosos hospitalizados com COVID-19 - Costa, Thaís Marques da (2022)
to carry out a systematic review of the literature on the prevalence of disease and diabetes mellitus in elderly people hospitalized with COVID-19. Method: the research strategy was designed according to the proposals by the MOOSE checklist, after registering the protocol in PROSPERO (CRD42022313931). Medline, Scielo, LILACS, SCOPUS, Web OF sCIENCE, Virtual Health Library (VHL) and Embase databases were consulted, using the primary descriptors “Aged”, “Dizziness”, “Hospitalization” and “COVID-19” were crossed with the secondary descriptor “Diabetes Mellitus, without language limitation and published between the years 2019 and 2022. Selection Criteria observational studies (case-control, cohort and cross-sectional), carried out with elderly hospitalized with or after COVID - 19 and who verify the prevalence of storms and diabetes mellitus. Studies outside these have been removed. Results: 168 articles were found, of which 8 were included. The prevalence of rotation was 5.27% (1.1%-18.25%) and the prevalence of Diabetes Mellitus was 14.63% (1.54%-29%) and the main associated factors were the increase age, male and hospital. The Newcastle-Ottawa Scale studies me with moderation and all methodological high quality. Conclusion: the trend towards age pattern was considered low in reference that diabetes mellitus was within an expected pattern. However, there is a need to standardize the estimates for this population and increase research regarding the presence of increased and these comorbidities in elderly hospitalized with COVID-19.